Trehalose promotes atherosclerosis regression in female mice - Robichaud, Sabrina; Rochon, Valérie; Emerton, Christina; Laval, Thomas; Ouimet, Mireille (Frontiers in Cardiovascular Medicine, 2024)
Introduction Atherosclerosis is a chronic inflammatory disease caused by the deposition of lipids within the artery wall. During atherogenesis, efficient autophagy is needed to facilitate efferocytosis and cholesterol efflux, limit inflammation and lipid droplet buildup, and eliminate defective mitochondria and protein aggregates. Central to the regulation of autophagy is the transcription factor EB (TFEB), which coordinates the expression of lysosomal biogenesis and autophagy genes. In recent years, trehalose has been shown to promote TFEB activation and protect against atherogenesis. Here, we sought to investigate the role of autophagy activation during atherosclerosis regression. Methods and results Atherosclerosis was established in C57BL/6N mice by injecting AAV-PCSK9 and 16 weeks of Western diet feeding, followed by switching to a chow diet to induce atherosclerosis regression. During the regression period, mice were either injected with trehalose concomitant with trehalose supplementation in their drinking water or injected with saline for 6 weeks. Female mice receiving trehalose had reduced atherosclerosis burden, as evidenced by reduced plaque lipid content, macrophage numbers and IL-1β content in parallel with increased plaque collagen deposition, which was not observed in their male counterparts. In addition, trehalose-treated female mice had lower levels of circulating leukocytes, including inflammatory monocytes and CD4+ T cells. Lastly, we found that autophagy flux in male mice was basally higher than in female mice during atherosclerosis progression. Conclusions Our data demonstrate a sex-specific effect of trehalose in atherosclerosis regression, whereby trehalose reduced lipid content, inflammation, and increased collagen content in female mice but not in male mice. Furthermore, we discovered inherent differences in the autophagy flux capacities between the sexes: female mice exhibited lower plaque autophagy than males, which rendered the female mice more responsive to atherosclerosis regression. Our work highlights the importance of understanding sex differences in atherosclerosis to personalize the development of future therapies to treat cardiovascular diseases.